The Role of Sustainable Competitive Advantage on Sustainable Finance and Bank Profitability - Valdiansyah, Riyan Harbi; Juanita Agustina R; Iswahyudi, Ari (Journal of Contemporary Accounting, 2024)
This study examines the moderating effect of sustainable competitive advantage on the relationship between sustainable finance and bank profitability of Indonesian conventional commercial banks from 2019 to 2022. The study has found that sustainable finance has a positive impact on bank profitability (ROA and ROE). However, the impact of sustainable competitive advantage on bank profitability was only positive with ROA, suggesting that ROA is a more effective indicator of bank profitability for this study. Furthermore, the study indicates that the impact of sustainable finance on bank profitability (both ROA and ROE) is diminished by the delay in the implementation of sustainability reporting during the COVID-19 reporting period. The results of this study are likely to encourage banks to increase their sustainable finance and focus on improving the quality of sustainability reporting in order to gain a competitive advantage in the current banking industry landscape in Indonesia.